Time-Dependent Growth of ZnO Nanowires Unveiling Antibacterial and Photocatalytic Properties - Abou Zeid, Souad (Langmuir : the ACS journal of surfaces and colloids, 2025)
This study investigates the synthesis, characterization, and functional properties of well-aligned zinc oxide (ZnO) nanowires (NWs) obtained by a two-step hydrothermal method. ZnO NWs were grown on silicon substrates precoated with a ZnO seed layer. The growth process was conducted at 90 °C for different durations (2, 3, and 4 h) to examine the time-dependent evolution of the nanowire properties. A comprehensive characterization of the ZnO NWs was performed using several analytical techniques. Scanning electron microscopy (SEM) revealed the morphological progression, specifically tracking changes in length and diameter as a function of the growth time. Ultraviolet (UV)-visible spectroscopy was employed to determine the optical band gap, while photoluminescence (PL) analysis provided insight into the concentration of structural defects and its evolution as a function of nanowire growth. The photocatalytic efficiency of the ZnO NWs was evaluated through the degradation of the organic dye methylene blue (MB) under UV light irradiation (365 nm). The kinetic of MB degradation was monitored for each growth time, with non-purgeable organic carbon (NPOC) analysis providing a detailed perspective on the photocatalytic activity over time. The antibacterial properties were tested against Pseudomonas putida, a Gram-negative bacterium, to determine the efficiency of the synthesized ZnO NWs as antimicrobial agents. The release of zinc ions (Zn2+), a key factor in the antibacterial mechanism, was quantified using inductively coupled plasma (ICP) analysis for each sample. By exploration of the relationship between the growth time, nanostructure morphology, and functional properties, this study provides insights into optimizing the synthesis of ZnO NWs for enhanced photocatalytic and antibacterial applications. These findings contribute to the development of advanced materials for environmental and biomedical applications